„Return to the Countryside” – The Retention Possibility of the Sport - Kőmíves, Péter Miklós; Szabados, György Norbert; Kulcsár, Gergely; Bácsné Bába, Éva; Fenyves, Veronika; Dajnoki, Krisztina (International Journal of Engineering and Management Sciences, 2018)
Nowadays, one of the most interesting parts of sociology is the research of the rural areas’ specific features. Within these studies the rural areas ability for survival and to retain forms an important basis. A basic pillar of these, that the youth from these areas become sufficiently motivated to return to their rural homeland after finishing their studies and be able to redound the local social and economic development. Sadly, we experience the opposite of it. Young generations are fleeing to large cities and in medium or long term it leads to the decay of these involved settlements; in worst case scenario the results can be irreversible. In close relation with the aforementioned, we have to mention the specific behaviour of the local – rural – elite, which can be the source of further problems. In the course of our research, we wanted to investigate, that what is the reason that university students, who are studying in large cities don’t want to return or move to rural areas. Furthermore, we tried to give an inside view about their opinions of rural areas and the life in the countryside.